2016
DOI: 10.1590/1678-457x.0012
|View full text |Cite
|
Sign up to set email alerts
|

Automated sugar analysis

Abstract: Sugarcane monosaccharides are reducing sugars, and classical analytical methodologies (Lane-Eynon, Benedict, complexometric-EDTA, Luff-Schoorl, Musson-Walker, Somogyi-Nelson) are based on reducing copper ions in alkaline solutions. In Brazil, certain factories use Lane-Eynon, others use the equipment referred to as "REDUTEC", and additional factories analyze reducing sugars based on a mathematic model. The objective of this paper is to understand the relationship between variations in millivolts, mass and teno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…The human body hosts complex microbial communities that play significant roles in physiology and disease [ 58 ]. Research has shown that the constant interaction between the intestinal microbiota and host is associated with certain types of inflammatory intestinal diseases, including ulcerative colitis and Crohn's disease [ 59 , 60 ]. Probiotic microorganisms (Lactobacillus species, Clostridium butyricum , Bifidobacterium, etc.)…”
Section: Recent Advances In the Use Of Hydrogels For Living Bacteria-...mentioning
confidence: 99%
“…The human body hosts complex microbial communities that play significant roles in physiology and disease [ 58 ]. Research has shown that the constant interaction between the intestinal microbiota and host is associated with certain types of inflammatory intestinal diseases, including ulcerative colitis and Crohn's disease [ 59 , 60 ]. Probiotic microorganisms (Lactobacillus species, Clostridium butyricum , Bifidobacterium, etc.)…”
Section: Recent Advances In the Use Of Hydrogels For Living Bacteria-...mentioning
confidence: 99%
“…In the Luff-Schoorl method, Cu 2+ ions which had not been reduced are determined iodometrically, while the reduced copper is determined in Lane-Eynon (Sá et al, 2018). Furthermore, total sugars are thence determined by converting nonreducing sugars into reducing sugars through acid or enzymatic hydrolysis (Marques et al, 2016;Tavares et al, 2010).…”
Section: Introductionmentioning
confidence: 99%